Effect of birthplace on infants with low birth weight. Issue 6553 (18th October 1986) - Beverley, D; Foote, K; Howel, D; Congdon, P
Abstract : From December 1983 to June 1985, 162 infants of less than 32 weeks' gestation or weighing less than 1, 500 g, or both, were cared for at the regional neonatal intensive care unit in Leeds. Of the 162, 64 (40%) were born in the unit because their mothers had received antenatal care there, 58 (36%) were born in another hospital and subsequently transferred, and 40 (25%) were transferred in utero because of potential complications. The overall mortalities for each group were 14%, 38%, and 18% respectively. These differences were significant, but when they were corrected for gestation, birth weight, and mode of delivery there was no difference in either the mortality or the incidence of intraventricular haemorrhage in the three study populations. Although there seem to be no distinct advantages of in utero transfer in terms of mortality and morbidity, there are other psychological and emotional advantages.